BUDAYA BAJAU : PEMANFAATAN DAN PELESTARIAN LINGKUNGAN - Indrawasih, Ratna; Antariksa, I.G.P (P2KK LIPI, 2003)
The specific life of Bajau’s people, have given them skills on maritime matters. Their skills not are only limited in managing marine resources, but in the past were also used by political and military power for marine’s security and across islands’ trading. This literature study discusses heavily on how the people of Bajau adapt to their environment in order to fulfil their living needs. These include the adaptation they made when living as wanderers in their boathouses on the sea, and the changes when they live permanently in coastal. Population distribution of the Bajaus, their identities and social structure are discussed to give comprehensive understanding about the Bajau people.